2015
DOI: 10.1021/acs.chemrestox.5b00067
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effect of Sulforaphane against Methylglyoxal Cytotoxicity

Abstract: Glycation, an endogenous process that leads to the production of advanced glycation end products (AGEs), plays a role in the etiopathogenesis of different neurodegenerative diseases, such as Alzheimer's disease (AD). Methylglyoxal is the most potent precursor of AGEs, and high levels of methylglyoxal have been found in the cerebrospinal fluid of AD patients. Methylglyoxal may contribute to AD both inducing extensive protein cross-linking and mediating oxidative stress. The aim of this study was to investigate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
64
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(66 citation statements)
references
References 98 publications
2
64
0
Order By: Relevance
“…Cells were grown in DMEM supplemented with 10% ( v / v ) of FBS, 2 mM glutamine, 50 U/mL of penicillin, and 50 μg/mL of streptomycin and maintained at 37 °C in a humidified incubator with 5% CO 2 as previously reported [64]. Cell differentiation was induced, reducing serum levels of the medium to 1% with 10 µM of RA for seven days prior to treatments.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cells were grown in DMEM supplemented with 10% ( v / v ) of FBS, 2 mM glutamine, 50 U/mL of penicillin, and 50 μg/mL of streptomycin and maintained at 37 °C in a humidified incubator with 5% CO 2 as previously reported [64]. Cell differentiation was induced, reducing serum levels of the medium to 1% with 10 µM of RA for seven days prior to treatments.…”
Section: Methodsmentioning
confidence: 99%
“…Cell viability was evaluated by measuring formazan formation as previously reported [64,65]. Briefly, after treatments, cells were incubated with 0.5 mg/mL of MTT solution for 1 h at 37 °C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Methylglyoxal (MG) is the major precursor in the formation of AGEs and has been reported to found in high concentrations in the cerebrospinal fluid of AD patients. [2] MG and its glycation products, both stimulating extensive protein cross-linking and triggering oxidative stress, causes several violent pathological incidents, especially in nervous tissue. [3,4] Glyoxalase-1 (GLO-1) system consists of two enzymes: GLO-1 and GLO-2 and represents the most effective defense system for the detoxification of cytotoxic MG and MG-derived AGEs.…”
mentioning
confidence: 99%
“…In a 2015 study, high levels of methylglyoxal have been found in the cerebrospinal fluid of Alzheimer patients. 719 In the same study, SFN was shown to enhance the methylglyoxal detoxifying system, increasing the expression and activity of GLO1 (glyoxalase -1) in a glutathione-dependent manner. As SFN demonstrated a protective anti-glycative effect in that study, one might postulate that the direction of expression of the Methylglyoxal pathway in the EASYGENEX Study was downregulation.…”
Section: Neurotransmitter Synthesis and Neuroprotectionmentioning
confidence: 91%